Teaching of the German language as a language of national minority in contemporary Poland = Nauczanie języka niemieckiego jako języka mniejszości narodowej we współczesnej Polsce - Pogorzała, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Teaching German as a language of national minority started in Poland in the early 1990s. Over the last twenty years, an increasing number of schools have introduced German as a subject in their curriculum. Here are bilingual classes too, but German is not used as an instructive language on a large scale. He main aim of the article is to analyse the policy of the Polish authorities towards German minority and the situation of German as a language of national minority in the system of education in Poland.
Keywords: German minority in Poland; teaching of minority languages in Poland; sustain ethnic identity; mniejszość niemiecka - Polska; nauczanie języków mniejszości w Polsce; podtrzymywanie tożsamości etnicznej